Degradasi Biksin Selama Pemanasan Dan Pencahayaan Degradation Of Bixin During Heating And Illumination - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT The kinetics of thermal and light induced degradation of natural bixin in a mixture of ethanol and 2 % acetic acid (80 : 20) was studied as a function of temperatures 80, 98, and 125 °C for 120 minutes. Illumination was carried out either underfluorescent or incandescent lights, both at 4000 lux for 300 minutes. The bixin concentration during heating and illumination was analysed using HPLC. The method to determine the degradation rate constant for the decay of the products from bixin was obtained using a linear regression according to first order reaction. The results indicated that the degradation rates of bixin at 125 °C were 5.5 and 3.8 times faster than that of 80 °C and 98 °C, respectively. The energy activation of bixin was 9.82 kcal/mol The photodegradation rate constants of bixin under incandescent orfluorescent illumination was 2.8 x 10-' and 3.3 x 104 minutes-', respectively.